Microsoft SQL Server 2012 reporting services - Larson, Brian (McGraw-Hill, 2012)
Including a detailed case study and sample reports; this practical reference covers the complete process of building and distributing reports and explains how to maximize all of the powerful; integrated SSRS capabilities; including the new and enhanced features. --